STUDENTS’ PERCEPTION AND ATTITUDE TOWARDS SCIENTIFIC WORK DURING UNIVERSITY STUDIES - Lokhvytska, Liubov; Martovytska, Nataliia; Kolomiiets, Olena; Demydenko, Tetyana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Strengthening the scientific component within the structure of the educational process in modern higher educational institutions in Ukraine has determined the task of clarifying students’ perception of the essence of conducting scientific work. The topicality of the research is determined by the fact that in the conditions of the current structure of university life, based on the principle of student-centeredness, students are autonomous subjects of study who participate in the educational process evaluation and improvement within the framework of the relevant curricula. The goal was to determine the perception and clarify the attitude of students towards the scientific work that is carried out in the university environment (based on the Ukrainian example) and to which they were involved during their studies. The following methods were used for its realization: theoretical (analysis, concretization, synthesis and systematization – while the scientific problem justification; generalization – for formulating the obtained results); empirical (written survey – questionnaire “Assessment of my scientific work during university study”); mathematical (calculation of the results). The article outlines three levels of students’ scientific work that takes place in the modern educational environment of the university: mastering the educational component “Fundamentals of Scientific Research”; involvement in various types of scientific work conducted in the system of higher educational institutions; carrying out research within the framework of the scientific subject-matter, scientific projects. The perception of students regarding the content and accomplishment of scientific work during their study at the university is presented, as well as recommendations for its improvement based on the results of the developed author’s questionnaire, which included 15 questions. Conclusions reveal the students’ awareness of the necessity for the scientific work tasks and their attitude towards their own participation as full-fledged subjects in the carrying out scientific research. The prospects of the raised problem will be the development of a strategy for improving student scientific work at the university through the prism of its evaluation by students.